Effectiveness of Resistance Training on Walking Speed among Geriatric Population - Bharathi, K.; Kumaresan, Abathsagayam; Arvindan, T.; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Vinodhkumar, Ramalingam; Ramana, Kameswaran (INTI International University, 2023)
Background and Aim: Muscle weakness is most related to slower walking pace and greater risk of impairment and slips in elderly. Walking speed is important component on balance and stability in older adults. Walking with lower acceleration and shorter step length is likely to greater risk of falling. The individual geriatric affected with low walking speed will be improved by resistance training program. The aim of research is to determine the effect of resistance training on walking speed among geriatric population. Method: The study conducted was Quasi-experimental studywith10 geriatrics conducted at Saveetha Medical College. The patients were assessed using spontaneous walking speed before and after treatment. The patients were given resistance training technique (30 minutes per session) for 3 sessions per day for 2weeks. Result: The statistical analysis reveals that p value <0.0001 is statistically significant. As result, the resistance training was found to be effective in geriatrics. Conclusion: The findings from this study indicated that resistance training technique is an efficacious intervention strategy to improve walking speed in geriatric population.